PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE SAS BERBANTUAN MEDIA FLASH CARD PADA SISWA KELAS I SD - Susilawati, Santi; Hamdani Maula, Luthfi; Azwar Uswatun, Din (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The early reading skills of first-grade students at Cipaku Public Elementary School are still relatively low due to a lack of variety in teaching methods and media. This study aims to improve early reading skills through the application of the SAS (Structural-Analytic-Synthetic) Method aided by flashcards. This study is a Classroom Action Research (CAR) based on the Kemmis and McTaggart design, conducted in two cycles. The research subjects consisted of 20 students (10 boys and 10 girls). Data collection techniques included observation, performance tests, and interviews, focusing on four aspects: pronunciation, clarity of voice, fluency, and comprehension. The results showed a significant improvement in classical learning achievement. In the pre-cycle, achievement reached only 45% (9 students) with scores above the minimum passing score (≥75). After the intervention, the percentage increased to 60% in Cycle I and reached 90% (18 students) in Cycle II, exceeding the 75% success target. This improvement aligns with the rise in the average scores across all assessment aspects from the pre-cycle to Cycle II: pronunciation (2.7 to 3.85), voice clarity (2.6 to 3.45), fluency (2.4 to 3.4), and comprehension (2.6 to 3.2). In conclusion, the integration of the structured stages of the SAS Method with flashcard visualization has proven effective in stimulating students’ focus and long-term memory; therefore, it is recommended as an innovative solution for improving early reading literacy in elementary schools.